Pseudoexfoliation syndrome (PEX) – a systemic disorder - Kurowska, Anna; Kamińska, Anna; Izdebska, Justyna; Szaflik, Jacek P.; Szaflik, Jerzy (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Pseudoexfoliation syndrome is an age-related elastosis. The current pathogenetic concept describes PEX as an elastic microfibrillopathy involving TGF-beta1, oxidative stress and impaired cellular protection mechanisms as a key pathogenetic factors. Extracellular PEX material is produced, aggregated and accumulated in the anterior segment of the eye. It is also present in the skin, lungs, liver and other visceral organs. These findings suggest that pseudoexfoliation syndrome is a systemic disorder. It is also associated with coronary artery disease, hypertension, Alzheimer’s disease and other cardio-vascular problems. The pseudoexfoliation syndrome has been found to be associated with higher mean intraocular pressure, secondary open-angle glaucoma, mature and nuclear cataract. Ocular depositions of pseudoexfoliation material can lead to many intraocular complications. That’s why special attention is required before, during and after surgery.